Personification in marketing communication: case study of Malaysian brands / Azahar Harun...[et.al] - Harun, Azahar; Abd Razak, Mohamed Razeef; Abd Rahim, Russlan; Mohd Radzuan, Lili Eliana; Abu Bakar, Amina Syarfina (2016)
This paper assesses the anthropomorphic forms depicted in four established Malaysian brands. They are Julie’s, Habib, Karangkraf and Happy Prepaid. In order to measure its effectiveness in brand design, a Visual Content Analysis approach is employed. This qualitative method which involves multiple case studies of selected brand design, analyzes the visual components of the selected brand design and extracting its underlying meaning. The findings show that each of the brand design contains variety of anthropomorphic forms which are unique and discernible. For the purpose of reference, we categorize each of the anthropomorphic forms as Literal, Partial, Abstract and Typographic. Literal means that the brand design exhibits almost accurate human character. Partial means that the brand shows certain part of human form like hands, head, eye, silhouette, etc. Abstract suggests that the brand exhibits conceptual human form. Typographic means that the brand design contains typefaces that display gesture or facial expression. Despite being distinctive, we also discover that the samples suggest meaningful expression, which can establish relationship with the consumers. We conclude that the anthropomorphic forms (Literal, Partial, Abstract and Typographic) found in the selected Malaysian brand design are not only meant for decorative reason but possess communicative value which is relevant in marketing and promotion.